Answer:
i do, but i just started.
Step-by-step explanation:
i think the answer is -50 but im
not sure
Answer:
Step-by-step explanation:
q is TFTF
~q use negation, not q so is the opposite of q : FTFT
p↔~q use biconditional ,and will be True only is both statements are T or both are F
p values are TTFF ↔~q values are FTFT : FTTF
(p↔~q )∧~q use conjunction, that is True only if both statements are T
(p↔~q ) values are FTTF ∧~q values are FTFT : FTFF
(p↔~q )∧~q → p use a conditional statement, where only True False will give a F
(p↔~q )∧~q values are FTFF → p values are TTFF : TTTT
I need more information to answer this question, so nobody can answer...